Numerical simulation of deformation and fracture in a coatedmaterial using curvilinear regular meshes; IOP Conference Series: Materials Science and Engineering; Vol. 71: International Scientific Conference of Young Scientists: Advanced Materials in Construction and Engineering 15-17 October 2014, Tomsk, Russia - Zinovjev A. V.; Balokhonov R. R. Ruslan Revovich; Martynov S. A.; Romanova V. A. Varvara Aleksandrovna; Zinovjeva O. S. (2015, 2015)
Title screen